THE TA'LIQAT METHOD OF SHEIKH SULAIMAN ARRASULI ON THE TAFSIR JALALAIN - Nasution, Muhammad Roihan; Hidayat, Muhammad; Rasyid, Muhammad (Journal of Contemporary Islam and Muslim Societies, 2023)
Abstract: This research departs from the discovery of manuscripts of interpretations of Nusantara scholars that have not received attention from a number of circles when the process of re-reading the interpretation of the Koran is rampant to meet the demands of human life development. This research aims to identify the manuscripts of the Nusantara scholars' tafsir and introduce their contents in order to preserve the richness of tafsir treasures in the archipelago. This research applies a philology-based qualitative method in which manuscripts are the main source with related tafsir books as the research subject. This research is classified as library research. It was found that Ta'liqat Sheikh Sulaiman Arrasuli is a commentary on Tafsir Jalalin by Imam Al-Mahalli and Imam Al-Suyuthi complete as many as 30 juz, although not all verses and interpretations were commented by him. Sheikh Sulaiman Arrasuli's commentaries are mostly about language; grammatical language, the meaning of the verse and there are also comments on the law, explanation of the story, asbabun nuzul and others, and most of the commentaries written by Sheikh Sulaiman Arrasuli. Keywords: Ta’liqat, Sheikh Sulaiman Arrasuli, Tafsir Jalalain